PENDAMPINGAN PENINGKATAN PRODUK UNGGULAN BERBAHAN BAKU BUAH NANAS DI DESA SAJAD KABUPATEN SAMBAS: Assistance For Improving Superior Products Made From Pineapple Fruit In Sajad Village, Sambas District - Kiki Kristiandi; Nurul Fatimah Yunita; Dewi Merdekawati; Oktavia Nurmawaty Sigiro; Maryono Maryono; Sangkala Sangkala; Sudirman Masara'T (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Pineapple fruit is a fruit that has distinctive characteristics ranging from aroma, color and shape. This fruit contains many nutrients that are beneficial to the body including bromyelin, vitamin C and other nutrients. This community service activity aims to improve the community's ability to utilize local food ingredients that have the potential to increase village superior products. The problem faced by Sajad Village is that there are frequent losses because agricultural products from pineapples tend to have lower prices to be sold to the market, besides that this loss also causes the motivation of the farmers to decrease. The preparations made in this activity are pineapple syrup, pineapple jam and shredded pineapple and packaging is done on preparations that have been processed. The method used in this community service is through outreach and training. After the training process was completed, each team evaluated the preparations that had been made and the testers were given the opportunity to give their opinion. Based on the activities that have been carried out, the community in Sajad Village, Sambas Regency, is satisfied and helped by the preparations that have been carried out. Another result that can be seen is that participants begin to understand that pineapple has many derivative preparations that can be utilized and are aware of the advantages of consuming pineapple.